Sabre Rattling in Space: A South Asian Perspective - Anum A. Khan (CISS Insight Journal, 2025)
The importance of outer space needs no emphasis, as it is discernible from competition amongst space powers. Meanwhile, the weaponization of global commons, especially outer space, vis-à-vis space securitization, is now debated in space policy discourse. Furthermore, space securitization is viewed through the prism of “Access to Space,” which is critical to the military and economic security of the “Nation States.” In this domain, Sabre-rattling in Space: A South Asian Perspective, co-authored by Ahmad Khan and Eligar Sadeh, is a timely book that articulates various subjects relevant to regional and global security. Khan has completed his PhD from the Department of Strategic Studies, National Defence University (NDU), Islamabad. Sadeh is a former space scientist at National Aeronautics and Space Administration (NASA). He has also served at the United States (US) Air Force Academy, Lockheed Martin, and the University of Colorado, US. This joint academic endeavor is the first-ever book written by a Pakistani and an American scholar on a highly important subject. This book is published by the Springer and comprises nine chapters and a conclusion.